2018
DOI: 10.1093/intimm/dxy070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the live oral attenuated typhoid vaccine, Ty21a, on systemic and terminal ileum mucosal CD4+ T memory responses in humans

Abstract: Mucosal CD4+ T memory responses after typhoid immunization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“…Here, we showed that the IFNγ and IL-17A are primarily produced by CD4+T RM (a subset of CD4+ T EM ) in significantly higher levels in the terminal ileum mucosa following Ty21a immunization. In addition, we observed that CD103+ CD4+T RM produced cytokines as monofunctional cells whereas CD103− CD4+T RM cells produced mostly multifunctional cytokines, similar to our observations in LPMC CD4+T EM [50]. These results suggest that examination of heterogeneous CD4+ T populations may mask the 'true' impact of oral Ty21a immunization due to the 'averaging effect' inherent to the analyses of whole populations/subsets which are composed of responding and non-responding cells.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Here, we showed that the IFNγ and IL-17A are primarily produced by CD4+T RM (a subset of CD4+ T EM ) in significantly higher levels in the terminal ileum mucosa following Ty21a immunization. In addition, we observed that CD103+ CD4+T RM produced cytokines as monofunctional cells whereas CD103− CD4+T RM cells produced mostly multifunctional cytokines, similar to our observations in LPMC CD4+T EM [50]. These results suggest that examination of heterogeneous CD4+ T populations may mask the 'true' impact of oral Ty21a immunization due to the 'averaging effect' inherent to the analyses of whole populations/subsets which are composed of responding and non-responding cells.…”
Section: Discussionsupporting
confidence: 87%
“…We have previously characterized S. Typhi-specific LPMC CD4+T EM cells and observed increasing trends in IFNγ and IL-17A production following Ty21a immunization [50]. Here, we showed that the IFNγ and IL-17A are primarily produced by CD4+T RM (a subset of CD4+ T EM ) in significantly higher levels in the terminal ileum mucosa following Ty21a immunization.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations